Editorial :PREVALENCE OF CELIAC DISEASE IN DEVELOPING COUNTRIES (Iraqi Journal of Medical Sciences, 2018)
Celiac disease (CD) is an autoimmune disorder, which affects genetically predisposed individuals upon the ingestion of gluten. So, it is the result of both environmental (gluten) and genetic factors (carriers of HLA-DQ2 and DQ8 haplotypes). A duodenal biopsy with positive serology is the gold standard for the diagnosis of CD. Celiac disease world geographical distribution seems to have followed the spread of wheat consumption in addition to the migratory flows of mankind. Following the application of simple serological tests for the diagnosis of CD in the 1980s, it gradually became clear that the prevalence of CD in different countries in the Middle East, North Africa and India is almost the same as that in Western countries. A high index of suspicion for CD should be maintained in all developing countries for patients who present with chronic diarrhea or iron deficiency anemia. The prevalence of CD varies with sex, age, and geographic location. The global prevalence of CD has increased over time from 0.6% in 1991 to 2000 to 0.8% between 2001 and 2016. According to that, there is a need for population-based prevalence studies in many developing countries especially middle east to estimate the burden of CD properly.Keywords: Celiac disease, gluten, HLA, prevalence, meta-analysis, Middle East, developing countries. Citation: Al-Shami SA. Prevalence of celiac disease in developing countries. Iraqi JMS. 2017; Vol. 15(4): 324-326. doi: 10.22578/IJMS.15.4.1
Keywords: Celiac disease; gluten; HLA; prevalence; metaanalysis; Middle East; developing countries